2022
DOI: 10.3390/foods11223614
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Beetroot Juice Ingestion on Neuromuscular Performance on Semi-Professional Female Rugby Players: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Purpose: Beetroot juice (BRJ) is considered an ergogenic aid with good to strong evidence for improving human performance in sport modalities with similar demands to rugby. However, most of the studies were realized in male athletes with limited evidence in female athletes. Thus, the aim of this study was to explore the acute ingestion of BRJ in female rugby players. Methods: Fourteen semi-professional female rugby players (25.0 ± 3.7 years) belonging to a team from the First Spanish Female Rugby Division part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
3
1
0
1
Order By: Relevance
“…The present study has been also unable to detect any effect of BRJ supplementation on jump height during CMJ after the Prone Yo-Yo IR1 test. This result is also in line with some, but not all (Clifford et al, 2016;López-Samanes et al, 2022b), studies that reported no effect of BRJ on the decrement in CMJ The main of time (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study has been also unable to detect any effect of BRJ supplementation on jump height during CMJ after the Prone Yo-Yo IR1 test. This result is also in line with some, but not all (Clifford et al, 2016;López-Samanes et al, 2022b), studies that reported no effect of BRJ on the decrement in CMJ The main of time (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, our findings provide a significant contribution regarding to the ergogenic potential of NO 3 ‐ supplementation over rugby‐specific exercise in trained rugby male players and in line with previous studies in different team‐sports athletes (i.e. basketball or hockey) that reported no ergogenic effect following acute BRJ supplementation (López‐Samanes et al, 2020; 2022a; 2022b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Significant differences were reported for salivary NO3-(593.4 vs. 8990.5 μM; p ≤ 0.001; ES = 4.15 [3.65;4.63]) (Figure 3A) and NO2-(219.9 vs. 5406.9 μM; p = 0.001; ES = 1.65 [1.31; 1.97]) (Figure 3B) concentrations between the placebo and BJ ingestion. Only 30% of the participants (3/10 participants) correctly identified the supplement that they had received (BJ or placebo), and there were limited side effects reported apart from few cases of increased fatigue or increased urine production (p = 0.330-1.000) (López Samanes at al., 2022). During the hours after completion of the neuromuscular test battery, rock climbers showed a similar prevalence of side effects in the two experimental protocols (BJ vs. placebo).…”
Section: Salivary No3-/no2-concentrations Side Effects Questionnaire ...mentioning
confidence: 99%
“…아이스하키 선수를 대상으로 통증 및 기능부전을 확인하여 체력 요인과의 관계를 검사 한 선행연구를 살펴보면, 엉덩 관절에 통증이 있는 선수는 낮은 엉덩 모음 근력을 보여주었다 (Oliveras et al, 2020). 또한, 엉덩 관절에 서 주관적 기능부전 점수와 모음과 벌림 근력 및 모음-벌림 근력 비 율과의 관계를 검사한 선행연구는 두 요소 간 매우 낮은 상관관계가 존재한다고 보고하여 (Wörner et al, 2019) & Olmsted-Kramer, 2007;Lawson et al, 2021;López-Samanes et al, 2022;Macht et al, 2016;Thompson et al, 2023) (Thompson et al, 2023).…”
unclassified